2010
DOI: 10.1074/jbc.m109.077230
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Translation of Heme Oxygenase-2 Preserves Human Endothelial Cell Viability during Hypoxia

Abstract: Heme oxygenases (HOs) -1 and -2 catalyze the breakdown of heme to release carbon monoxide, biliverdin, and ferrous iron, which may preserve cell function during oxidative stress. HO-1 levels decrease in endothelial cells exposed to hypoxia, whereas the effect of hypoxia on HO-2 expression is unknown. The current study was carried out to determine if hypoxia alters HO-2 protein levels in human endothelial cells and whether this enzyme plays a role in preserving their viability during hypoxic stress. Human umbil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 44 publications
(45 reference statements)
1
29
0
Order By: Relevance
“…HO-1 expression has been demonstrated to be associated with prostate cancer progression [56]. In addition, it has been shown that selective inhibition of HO-2 by siRNA increases reactive oxygen species and activates caspases inducing apoptotic cell death [57], but up to date, the role of HO-2 in cancer is almost unexplored. Results reported in the present study evidenced, for the first time, the ability of EA to decrease the expressions of HO-1 and HO-2, both representative of one of the most important cytoprotective system in the cell.…”
Section: Resultsmentioning
confidence: 99%
“…HO-1 expression has been demonstrated to be associated with prostate cancer progression [56]. In addition, it has been shown that selective inhibition of HO-2 by siRNA increases reactive oxygen species and activates caspases inducing apoptotic cell death [57], but up to date, the role of HO-2 in cancer is almost unexplored. Results reported in the present study evidenced, for the first time, the ability of EA to decrease the expressions of HO-1 and HO-2, both representative of one of the most important cytoprotective system in the cell.…”
Section: Resultsmentioning
confidence: 99%
“…HO-2, for example, is a survival factor in the endothelium as shown by the observations that HO-2 deficiency exacerbates apoptosis of endothelial cells incurred by either glutamate or TNF-␣ (3,34), whereas increased amounts of HO-2 protein reduce the lethal effects of hypoxia in endothelial cells (18). Deficiency of HO-2 promotes the appearance of an activated phenotype in aortic endothelial cells (4), and following the wounding of the corneal epithelium, deficiency of HO-2 enhances inflammatory responses and impairs reparative responses (5,17).…”
Section: Discussionmentioning
confidence: 96%
“…HO-2 deficiency, for example, leads to an activated phenotype in aortic endothelial cells (7), and promotes glutamate-induced or TNF-␣-induced apoptosis in cerebral endothelial cells (5,27); increased amounts of HO-2 protein protects endothelial cells against hypoxia (17); HO-2 deficiency adversely affects inflammatory and reparative responses following corneal wounding (16,34); finally, genetic deficiency of HO-2 exacerbates diabetes-induced renal injury in the streptozotocin murine model (15). However, prior studies demonstrate that cortical neuronal cultures and striatal cells from HO-2 Ϫ/Ϫ mice are relatively resistant to the cytotoxic effect of hemoglobin (31,32), while intracerebral injection of blood induces less cytotoxicity and oxidative stress in HO-2 Ϫ/Ϫ mice (30); in contrast, genetic deficiency of HO-2 increases the sensitivity of astrocytes to hemin (9).…”
Section: Discussionmentioning
confidence: 99%